Risk factors and quality of life of dyslipidemic patients in Lebanon: A cross-sectional study - Akram Farhat; Amal Al-Hajje; Samar Rachidi; Salam Zein; Mayssam Bou Zeid; Pascale Salameh; Wafaa Bawab; Sanaa Awada (Springer, 2019)
The main objective of this study was to identify the risk factors of dyslipidemia and measure its impact on patients' quality of life (QOL). Secondary objectives were to determine the percentage of dyslipidemia and assess the predictive factors affecting patients' QOL. A cross-sectional study was conducted in a sample of Lebanese population. A standardized questionnaire was developed to assess the QOL using the Short form-36 (SF-36) score. A total of 452 individuals were interviewed, of which 59.5% were females. The mean age was 43.3 ± 15.6 years, and 24.8% had dyslipidemia. The results show a lower overall QOL score among dyslipidemic patients compared with controls (57.9% and 76.5%, respectively; p < 0.001). Waterpipe smoking [adjusted odds ratio (ORa) = 4.113, 95% confidence interval (CI): 1.696-9.971, p = 0.002], hypertension (ORa = 3.597, 95% CI: 1.818-7.116, p < 0.001), diabetes (ORa = 3.441, 95% CI: 1.587-7.462, p = 0.002), cigarette smoking (ORa = 2.966, 95% CI: 1.516-5.804, p = 0.001), and passive smoking (ORa = 2.716, 95% CI: 1.376-5.358, p = 0.004) were significantly associated with dyslipidemia in individuals older than 30 years. A higher overall QOL score (p = 0.013) was observed in patients treated with statins in comparison with other lipid-lowering medications. In addition to clinical and economical consequences, dyslipidemia may have a significant impact on patients' QOL. Further research is needed to confirm the impact of treatment on dyslipidemic patients' QOL in order to maximize the overall benefits of therapy.